Cup orientation following posterior approach THA – the effect of different visual aids and pelvic supports - Innmann, Moritz M.; Verhaegen, Jeroen; Merle, Christian; Beaulé, Paul E.; Meermans, Geert; Grammatopoulos, George (Université d'Ottawa | University of Ottawa, 2022)
Abstract Introduction This study aims to compare cup inclination achieved (1) Using two orientation guides, whilst using the same 3-point pelvic positioner and (2) Using two types of pelvic positioners, whilst measuring intra-operative cup inclination with an inclinometer. Materials and methods This is a prospective, diagnostic cohort study of a consecutive series of 150 THAs performed through a posterior approach. Two types of 3-point pelvic positioners were used (Stulberg and modified Capello Hip Positioners) and the cup was positioned freehand using one of two orientation guides (mechanical guide or digital inclinometer). Intra-operative inclination was recorded, radiographic cup inclination and anteversion were measured from radiographs. The differences in inclination due to pelvic position (ΔPelvicPosition) and orientation definitions (ΔDefinition) were calculated. Target radiographic inclination and anteversion was 40/20° ± 10°. Results There was no difference in radiographic cup inclination/ (p = 0.63) using a mechanical guide or digital inclinometer. However, differences were seen in ΔPelvicPosition between the positioners ((Stulberg: 0° ± 5 vs. Capello: 3° ± 6); p = 0.011). Intra-operative inclination at implantation was different between positioners and this led to equivalent cases within inclination/anteversion targets (Stulberg:84%, Capello:80%; p = 0.48). Conclusions With the pelvis securely positioned with 3-point supports, optimum cup orientation can be achieved with both alignment guides and inclinometer. Non-optimal cup inclinations were seen when intra-operative inclinations were above 40° and below 32°, or the ΔPelvicPosition was excessive (> 15°; n = 2). We would thus recommend that the intra-operative cup inclination should be centered strictly between 30° and 35° relative to the floor. Small differences exist between different type of pelvic positioners that surgeons need to be aware off and account for.